Effects of F-Strain Mycoplasma gallisepticum Inoculation at Twelve Weeks of Age on Serum Vitellogenin Concentrations in Commercial Egg Laying Hens - Peebles , E.D.; Burnham, M.R.; Branton, S.L.; Willeford, K.O.; Gerard, P.D. (International Journal of Poultry Science, 2012)
The objective for this study was to determine if circulating vitellogenin (VTG) concentrations throughout a complete egg laying cycle in commercial layers are affected by a pre-lay inoculation of F-strain Mycoplasma gallisepticum (FMG). At 20, 28, 32, 36, 40, 44, 48 and 52 wk of age, blood was collected and serum was extracted for analysis of VTG concentration in layers that had either been sham-inoculated (control) or inoculated with FMG at 12 wk of age. Ten birds were housed in each of 8 biological isolation units with 4 replicate units per treatment. Each wk, sera from 4 independently tagged birds in each unit were pooled for analysis. The molecular weight of VTG in the pooled serum samples from each unit was estimated by comparison with the electrophoretic mobilities of proteins of known molecular weight in polyacrylamide gels. Additional comparisons were made using serum from estrogenized roosters known to have elevated VTG concentrations. Electrophoretic image analysis and VTG quantitation were determined via a multi-image analyzer and associated software. The effects of bird age, FMG treatment and their interactions on VTG concentration were determined. There was a significant main effect due to hen age on serum VTG concentration; however, FMG treatment had no significant effect on serum VTG concentration throughout the lay cycle. Therefore, it was concluded that the effects exerted by FMG on layer performance and egg yolk composition, as noted in previous research, may not be attributed to the influences of FMG on serum VTG concentrations.